Magic Ritual Saluang Dendang Sarisompak in Nagari Taeh Baruah - Delvia Mona; Wadiyo Wadiyo; Suharto Suharto; Ardipal Ardipal (Universitas Negeri Semarang, 2023)
Saluang dendang Sirompak lives and develops in the Taeh community, Fifty Cities District, which is considered a musical art that is a magical ritual. If we reflect on Islamic teachings, this Sirompak has greatly deviated from Islamic teachings, but until now there are still people who defend it, and conversely there are quite a lot of people who oppose the Sirompak tradition. Saluang dendang Sirompak has several musical elements such as rhythm, poetry, melody, and scales. Saluang Sirompak has a loose rhythm and very rarely puts pressure on the rhythm, while the lyrics contain spells to function to cast spells on the target person who will be assisted by spirits, and the resulting melodies are accompaniment to chants or spells sung by the performer, ladder the tone used is a minor scale that seems mystical, this is what causes Saluang Sirompak to seem mystical and many people are afraid to hear this Saluang Sirompak melody. The beauty of Sirompak's melodies with a magical background has always been positioned as a sound aesthetic that is still considered taboo to be developed beyond the mystical function it carried in the past. Currently sirompak has begun to be developed as an art form with the format of folk performing arts.